Isoprenaline protects intestinal stem cells from chemotherapy‐induced damage. (3rd January 2020) - Zeng, Huihong; Li, Huan; Yue, Mengzhen; Fan, Ying; Cheng, Jiaoqi; Wu, Xincheng; Xu, Rui; Yang, Wuping; Li, Manjun; Tang, Jiahui; Chen, Hongping; Kuang, Bohai; et al.
Abstract : Background and Purpose: Damage to intestinal epithelial cells and mucosa limits the effectiveness of several anti‐cancer chemotherapeutic agents but the underlying mechanism (s) remain unknown. Little is known of how enteric nervous system regulates proliferation, differentiation, impairment, and regeneration of intestinal stem cells. Here we have investigated the effects of isoprenaline on the damaged intestinal stem cells induced by chemotherapeutic treatments in mice. Experimental Approach: The effects of inhibiting sympathetic and parasympathetic nerves on intestinal stem cells were examined in male C57BL/6J mice. Protection by isoprenaline of intestinal stem cells was assessed in the presence or absence of 5‐fluorouracil (5FU) or cisplatin. Cellular apoptosis, cell cycle, PI3K/Akt signalling, and NF‐κB signalling in intestinal stem cells were mechanistically evaluated. Key Results: The sympathetic nerve inhibitor 6‐OHDA decreased the number and function of intestinal stem cells. 5FU or cisplatin treatment damaged both intestinal stem cells and sympathetic nerves. Notably, isoprenaline accelerated the recovery of intestinal stem cells after 5FU or cisplatin treatment. This protective effect of isoprenaline on damaged intestinal stem cells was mediated by β2 ‐adrenoceptors. The benefits of isoprenaline were mainly mediated by inhibiting cellular apoptosis induced by 5FU treatment, which might contribute to fine‐tuning regulating NF‐κB signalling pathway by isoprenaline administration. Conclusions and Implications: Treatment with isoprenaline is a new approach to ameliorate the damage to intestinal stem cells following exposure to cancer chemotherapeutic agents.